Processing of facial expressions of emotions in Antisocial, Narcissistic, and Schizotypal personality disorders: An event-related potential study. (September 2016) - Zhang, Bingren; Shen, Chanchan; Zhu, Qisha; Ma, Guorong; Wang, Wei
Abstract: Background: Antisocial, Narcissistic and Schizotypal personality disorders share dissocial traits, but have different impairments when recognizing facial emotions. Whether the differences are due to the early perceptual or late cognitive cerebral processes remains unknown. Methods: We invited 12 patients with Antisocial, 13 with Narcissistic, 12 with Schizotypal personality disorder, and 25 healthy volunteers, to undergo the cerebral event-related potentials to facial expressions of Neutral, Anger, Happiness, and Sadness, and the anxiety and depression measures. Results: Compared with healthy volunteers, reaction time to Happiness was prolonged in people with Narcissistic personality disorder; P3b amplitude to Sadness was smaller in people with Antisocial personality disorder. P2 amplitudes to Neutral and Happiness were negatively correlated with depression in people with Narcissistic personality disorder, and P3a and P3b latencies to Happiness were delayed in people with Schizotypal personality disorder relative to healthy volunteers. Conclusions: When responding to facial emotions, the attention or cerebral process was shallow in Antisocial, emotionally-affected in Narcissistic, and time-expanded in Schizotypal patients. Highlights: Mobilized attentional resources in Antisocial patients are more shallow. Cerebral processes in Narcissistic patients are more affected by mood states. Time period of mental processes in Schizotypal patients are prolonged.